2017
DOI: 10.1038/s41598-017-02802-0
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of human dermal fibroblasts in vitro: decisive role of cell culture conditions and treatment protocols on experimental outcome

Abstract: Photobiomodulation-based (LLLT) therapies show tantalizing promise for treatment of skin diseases. Confidence in this approach is blighted however by lamentable inconsistency in published experimental designs, and so complicates interpretation. Here we interrogate the appropriateness of a range of previously-reported treatment parameters, including light wavelength, irradiance and radiant exposure, as well as cell culture conditions (e.g., serum concentration, cell confluency, medium refreshment, direct/indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 55 publications
(72 reference statements)
4
50
0
Order By: Relevance
“…Therefore, the observation of photorejuvenation, wound healing or hair regrowth effects cannot yet be associated with a stimulation/inhibition of a particular cell type, for example, dermal fibroblasts. Some of our results concurred with previous research studies . In particular, it was clear that three consecutive exposures to short visible wavelengths (⇐530 nm), exerted inhibitory effects on DFs while long visible and NIR wavelengths (>=530 nm) had a neutral impact at standard environmental oxygen concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the observation of photorejuvenation, wound healing or hair regrowth effects cannot yet be associated with a stimulation/inhibition of a particular cell type, for example, dermal fibroblasts. Some of our results concurred with previous research studies . In particular, it was clear that three consecutive exposures to short visible wavelengths (⇐530 nm), exerted inhibitory effects on DFs while long visible and NIR wavelengths (>=530 nm) had a neutral impact at standard environmental oxygen concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Reduced proliferation and metabolic activity has also been observed in primary cultures of human dermal fibroblasts after irradiation with blue light . Recently, Mignon et al demonstrated a stimulatory effect with a single treatment of 450 nm light at 2 J/cm 2 on metabolic activity of dermal fibroblasts, with suppressive action following additional irradiations . In a scratch‐wound assay, high‐dose blue light (55 J/cm 2 ) inhibited fibroblast migration, while lower doses (2, 5, and 10 J/cm 2 ) had no effect .…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, however, the same dose of blue light was shown to have differential effects on distinct lineages of human dermal fibroblasts . In addition to differential biological responses elicited by different cell lineages and irradiation parameters, identifying effective therapeutic parameters for blue light‐based therapies is further complicated by the still incomplete knowledge of the photoacceptors in the skin . Besides nitrosated proteins, the effects of blue light could be mediated by photoacceptors in mitochondria, including cytochrome c oxidase, but also by cryptochromes and other flavoproteins, and all could lead to the generation of NO and reactive oxygen species (ROS) or to the activation of G‐protein‐coupled receptors .…”
Section: Introductionmentioning
confidence: 99%